Examining The Role of Emotional Intelligence in Enhancing Teacher-Student Relationships and Classroom Management - Kaur, Preetinder (Journal of Neonatal Surgery, 2025)
This research delves into the ways emotional intelligence (EI) affects these connections, with a focus on how it affects classroom atmosphere, communication, empathy, and conflict resolution. Emotional intelligence, or EI, is widely recognized as a crucial factor in fostering productive relationships between educators and students. An essential component of emotional intelligence (EI) is the capacity to recognize, categorize, and control one's own and other people's emotional states. During interactions between the two parties, teachers who practice emotional intelligence are better able to comprehend their students' points of view and meet their needs with compassion. Adults can help children thrive in an environment that is accepting when they can put themselves in the other person's shoes. The capacity to communicate clearly and concisely with students is essential to EI in the classroom. In order to establish rapport with their students, educators with high EI scores are able to express themselves precisely, pay close attention to what is being said, and adapt their language. By facilitating meaningful conversations, this encourages student engagement and participation in classroom activities. Additionally, EI assists educators in developing skills in conflict resolution and emotion management. By maintaining a positive emotional state and acting in a positive manner, teachers can encourage their students to work on developing their own emotional intelligence and social skills. Research shows that classes taught by professors who are emotionally aware improve students' academic and behavioral performance as well as their social and emotional health. Students' intrinsic motivation to study, resilience in the face of adversity, and constructive peer interaction are all linked to such classrooms. In conclusion, educators need to have a high level of emotional intelligence in order to create strong connections between them and their students, which in turn improves their academic performance. If educators want to create a welcoming classroom for all students, they must incorporate emotional intelligence (EI) into their lessons in order to recognize the importance of students' social and emotional development in addition to their academic performance...